Entrepreneurship and Digital Orientation in Enhancing SME Performance Mediated by Marketing Capabilities - Trisnawati Trisnawati; Alhidayatullah Alhidayatullah; Antony Antony (Lafadz Jaya Publisher, 2024)
Research on entrepreneurial and digital orientation in improving the performance of MSMEs has been carried out a lot, but there are still few variables in marketing capabilities used as mediation. This study's objective is to examine and explain the influence of entrepreneurial and digital orientation in improving the performance of MSMEs mediated by marketing capabilities. Quantitative research methodology is applied. The study's population is 14,128 food MSMEs in Sukabumi City, while the sample is taken using raosoft.com sample size calculator with a distribution rate of 50%, and the criteria are to have a business capital of Rp.1,000,000-15,000,000 and a business duration of 3-6 years or more, so that as many as 96 business actors were obtained as a sample. A Google Form is used to distribute questionnaires as part of the data collection technique SEM PLS is the analytical method employed. The results of the study explained that there was a significant influence shown by the value of the determination coefficient, the influence on the performance of MSMEs was 70.3% while the influence on marketing capcapability was 41.1%. This research's contribution is to offer an overview to business actors and DISKUMINDAG in making appropriate policies, as well as to help future researchers who will conduct similar research.